Obesity among Scottish 15 year olds 1987-2006: prevalence and associations with socio-economic status, well-being and worries about weight - West Patrick; Sweeting Helen; Young Robert (BMC, 2008)
Abstract Background Increases in the prevalence of child and adolescent obesity have accelerated since the mid 1980s. Socio-economic status (SES)-adiposity relationships appear less clear in adolescence than childhood, and evidence on whether increasing obesity is itself patterned according to SES is inconsistent. Increasing prevalence may have increased the tolerance, and reduced recognition of, or concern about, obesity. The aim of this study is to report the prevalence of obesity and its association with SES, well-being and worries about weight among 15-year olds in 1987, 1999 and 2006. Methods Height and weight data obtained from 15-year olds in 1987 (N = 503), 1999 (N = 2,145) and 2006 (N = 3,019), allowed categorisation of obesity (UK90 criteria). SES was represented by parental occupational class and area deprivation; psychological wellbeing by the 12-item General Health Questionnaire (GHQ-12) and self-esteem; weight worries by 'a lot' of worry about weight. Results Obesity prevalence was 6.7%, 10.6% and 15.9% (males), and 5.4%, 11.5% and 14.9% (females) in 1987, 1999 and 2006. Among obese males, BMIs increased over time. There was little evidence of differentials in obesity in respect of either SES measure, and none for increased disparities over time. There was no association between obesity and GHQ-12 'caseness' or (except females in 2006) self-esteem. Weight worries were more prevalent among the obese and increased over time overall, but the obesity-weight worry relationship did not change. At each date, large proportions of the obese did not worry 'a lot' about weight, while among the non-obese, up to 18.8% males and 40.1% females (in 2006) did worry. Conclusion Between 1987 and 2006, prevalence of obesity among Scottish 15 year olds increased around 2.5 times. However, this increasing prevalence did not impact on the obesity-weight-worry relationship. While many obese adolescents appear unconcerned about their weight, a significant minority of the non-obese worry needlessly.